Introducing a mindfulness-based intervention in school curriculum to 16–24-year-olds. A nationwide cluster-randomized trial - Lise Juul; Morten Frydenberg; Emilie Hasager Bonde; Michelle Sand Beck; Katinka Goetzsche; Susanne Bruggisser; Lone Overby Fjorback (npj Mental Health Research)
Abstract The aim was to assess the effectiveness of an intervention comprising a teacher-training program and the implementation of a ten-session mindfulness-based intervention (MBI) in regular classroom teaching for 16- to 24-year-old students in Denmark. In a cluster-randomized trial (2019-2021), upper secondary schools and vocational schools for social and health care were randomly assigned 1:1 to receive the intervention (21 schools, 35 teachers, 438 students) or teaching-as-usual (22 schools, 38 teachers, 551 students). Eighteen self-report measures of mental health were collected at baseline, three, and six months, with the Warwick-Edinburgh Mental Well-Being Scale (SWEMWBS) as the primary outcome. Intention-to-treat analyses were conducted using mixed-effects linear regression and bootstrapping. Fourteen intervention schools (n = 277) and 17 teaching-as-usual schools (n = 419) provided follow-up data. No statistically significant effect on the primary outcome (SWEMWBS) was found in the total population. However, a small positive effect on SWEMWBS was observed among females in upper secondary schools at three months, but not sustained at six months. Trial Registration: ClinicalTrials.gov Identifier: NCT04610333, registered October 26, 2020, https://clinicaltrials.gov/ct2/results?cond=&term=NCT04610333&cntry=&state=&city=&dist= .